Family Support and Its Association with Glycemic Control in Adolescents with Type 1 Diabetes Mellitus in Riyadh, Saudi Arabia - Adwa M. AlHaidar; Norah A. AlShehri; Munira A. AlHussaini (Journal of Diabetes Research)
The prevalence of type 1 diabetes mellitus (T1DM) among children in Saudi Arabia is increasing with unfavorable outcomes. Therefore, in addition to pharmacotherapy, other measures should be studied regarding psychological aspects mainly among adolescents. The family, which acts as the primary caregiver at this age, may play a major role in disease management. Thus, this study is aimed at assessing the perception of adolescents about the behaviors of their families initially and at investigating the correlation between these behaviors and glycemic control. Up to our knowledge, there was no study in Saudi Arabia that addressed this issue previously. This cross-sectional observational study assessed adolescents aged 10–19 years diagnosed with T1DM on insulin and receiving follow-up care at the King Saud University Medical City in Riyadh, Saudi Arabia. Data were collected via telephone interview and the verified “Modified Diabetes Social Support Questionnaire-Family version”. Glycemic control was then assessed using the most recent hemoglobin A1c (HbA1c) level recorded in their electronic files. Fifty-six adolescents participated in this study with an equal sex distribution (each n=28). Almost all participants were Saudis, and the majority were living in Riyadh (n=41). The mean age was 16.1±2.41 years with a mean of 6.1±4.14 years history of diabetes. The mean HbA1c level was 9.6±2.12%. Participants perceived all behaviors as supportive with “support in critical situations” being the highest (77.3%) and the only factor significantly related to HbA1c (p=0.017). Age was significantly related to all factors (p>0.05). Family plays a major role in the management of diabetes. Their supportive behaviors are perceived by their family members diagnosed with T1DM, but there has been no optimal association with disease control. However, the involvement of the family can aid in decreasing possible complications of the disease by intervening in critical situations.